A puzzle form of a non-verbal intelligence test gives significantly higher performance measures in children with severe intellectual disability - Crewther Sheila G; Goharpey Nahal; Bello Katrina D; Crewther David P (BMC, 2008)
Abstract Background Assessment of 'potential intellectual ability' of children with severe intellectual disability (ID) is limited, as current tests designed for normal children do not maintain their interest. Thus a manual puzzle version of the Raven's Coloured Progressive Matrices (RCPM) was devised to appeal to the attentional and sensory preferences and language limitations of children with ID. It was hypothesized that performance on the book and manual puzzle forms would not differ for typically developing children but that children with ID would perform better on the puzzle form. Methods The first study assessed the validity of this puzzle form of the RCPM for 76 typically developing children in a test-retest crossover design, with a 3 week interval between tests. A second study tested performance and completion rate for the puzzle form compared to the book form in a sample of 164 children with ID. Results In the first study, no significant difference was found between performance on the puzzle and book forms in typically developing children, irrespective of the order of completion. The second study demonstrated a significantly higher performance and completion rate for the puzzle form compared to the book form in the ID population. Conclusion Similar performance on book and puzzle forms of the RCPM by typically developing children suggests that both forms measure the same construct. These findings suggest that the puzzle form does not require greater cognitive ability but demands sensory-motor attention and limits distraction in children with severe ID. Thus, we suggest the puzzle form of the RCPM is a more reliable measure of the non-verbal mentation of children with severe ID than the book form.